2022
DOI: 10.1371/journal.pone.0267125
|View full text |Cite
|
Sign up to set email alerts
|

Portopulmonary hypertension and the risk of high right ventricular systolic pressure in liver transplant candidates

Abstract: Aim Portopulmonary hypertension (PoPH) is a rare and serious complication of liver cirrhosis and portal hypertension that can interfere with liver transplantation (LT). We evaluated the prevalence of PoPH and the clinical features of right ventricular systolic pressure (RVSP), which is equivalent to pulmonary artery systolic pressure, in LT candidates. Methods This was a single-center retrospective study. A total of 157 Japanese patients with decompensated liver cirrhosis or portal hypertension (76 men, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Yoshimaru et al [ 25 ] reported that patients with PoPH had a significantly higher BNP level, which was predictive of asymptomatic PoPH, with an optimal cut-off value of 29.1 pg/mL. In our data, it was 90.8 pg/mL in patients with RVSP ≥ 36 mmHg [ 6 ]. Out of seven HPS patients, we measured serum BNP in five patients.…”
Section: Clinical Features Of Pophsupporting
confidence: 49%
See 1 more Smart Citation
“…Yoshimaru et al [ 25 ] reported that patients with PoPH had a significantly higher BNP level, which was predictive of asymptomatic PoPH, with an optimal cut-off value of 29.1 pg/mL. In our data, it was 90.8 pg/mL in patients with RVSP ≥ 36 mmHg [ 6 ]. Out of seven HPS patients, we measured serum BNP in five patients.…”
Section: Clinical Features Of Pophsupporting
confidence: 49%
“…McDonnell et al [ 2 , 3 ] showed a prevalence of histopathological changes of 0.61% in autopsies of patients with liver cirrhosis (LC), and PoPH is the fourth most common condition (approximately 10%) among PAH cases [ 2 ]. Recent cohort studies showed prevalence rates of PoPH of 1–6% in patients presenting to be evaluated for liver transplantation (LT) [ 3 , 4 , 5 , 6 ]. Patients with PoPH have an increased risk of death; their reported death rates without therapy at 1 and 5 years were 54% and 86%, respectively [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As reported, plasma BNP parameters are bound up with pulmonary hypertension and cardiac function in patients with chronic obstructive pulmonary disease (COPD) and pulmonary heart disease, implying that BNP could reflect the health condition of patients and guide their treatment 21 . A study including 157 patients with portal hypertension or decompensated cirrhosis has disclosed that BNP levels are elevated in patients with high right ventricular systolic pressures, thus predicting portopulmonary hypertension (PoPH) 22 . Moreover, BNP measurement has been demonstrated to have utility in the early diagnosis of PoPH, with a cut‐off value of 29.1 pg/mL for BNP in the prediction of the disease 23 …”
Section: Discussionmentioning
confidence: 98%
“…21 A study including 157 patients with portal hypertension or decompensated cirrhosis has disclosed that BNP levels are elevated in patients with high right ventricular systolic pressures, thus predicting portopulmonary hypertension (PoPH). 22 Moreover, BNP measurement has been demonstrated to have utility in the early diagnosis of PoPH, with a cut-off value of 29.1 pg/mL for BNP in the prediction of the disease. PTX3 is a novel and effective biomarker for the assessment of patients with PAH.…”
Section: Discussionmentioning
confidence: 99%